Relationship between viscosity change and specificity in protein binding reaction studied by high-frequency wireless and electrodeless MEMS biosensor. (19th May 2015) - Shagawa, Tomohiro; Torii, Hiroomi; Kato, Fumihito; Ogi, Hirotsugu; Hirao, Masahiko
Abstract: This study proposes a methodology for evaluating specific binding behavior between proteins using a resonance acoustic microbalance with a naked-embedded quartz (RAMNE-Q) biosensor. We simultaneously measured the frequency responses of fundamental (58 MHz) and third-order (174 MHz) modes during multi step injections of proteins and deduced the thickness and viscosity evolutions of the protein layer. The viscosity increases with the progress of the binding reaction in nonspecific binding, but it markedly decreases in specific-binding cases. Thus, the high-frequency RAMNE-Q biosensor can be a powerful tool for evaluating specificity between proteins without measuring dissipation.